2018
DOI: 10.1016/j.fertnstert.2018.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pain tolerance is decreased and independent of clinical pain intensity in patients with endometriosis

Abstract: Objective: To investigate alterations in tactile, pain thresholds and pain tolerance thresholds in patients with endometriosis using a multimodality approach. Design: Cross-sectional study. Setting: Multidisciplinary referral center. Patient(s): Women with proven endometriosis (N ¼ 35) and healthy controls (N ¼ 38). Intervention(s): Pain processing was tested using quantitative sensory testing (QST) to investigate sensation, pain, and pain tolerance thresholds for thermal, electrical, and pressure stimuli. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Dysmenorrhea appears to be highly prevalent in young women and to decrease with age. This may be partly explained by medication and advice used by women to cope with their pain [ 26 , 27 ]. Another hypothesis is that subsequent pregnancies and deliveries, occurring later, may also reduce dysmenorrhea, which could explain this linear decrease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysmenorrhea appears to be highly prevalent in young women and to decrease with age. This may be partly explained by medication and advice used by women to cope with their pain [ 26 , 27 ]. Another hypothesis is that subsequent pregnancies and deliveries, occurring later, may also reduce dysmenorrhea, which could explain this linear decrease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 We also found that some women experienced constant pain that increased in intensity during menstruation and for others pain started as cyclical but worsened to be more severe, 33 persistent and pervasive, which has been linked to poor quality of life. 47 Research has suggested that experiencing pain may lead to sensitisation of the nervous system 12,13,48 recognised as a reason for pain to become more pervasive over time 49 however, participants believed that their endometriosis was worsening.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that intensity did not always relate to how intrusive pain was to everyday life. 48 Some less intense pain was experienced as more difficult to manage. Research has suggested that these differences in attentional focus are important in understanding how pain affects lives because severe pain can consume every experience 50 or prevent attention being paid to other aspects of experience leading to suffering.…”
Section: Conceptual Understanding Of Endometriosis-related Painmentioning
confidence: 99%
“…It has been shown that women with endometriosis experience a decreased pain threshold and therefore a higher pain perception after noxious stimuli [ 17 ]. However, studies of patients with CPP have shown similar findings [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%